Fertilizer pricing policy in Bangladesh - Stone, Bruce (International Food Policy Research Institute, 1987)
These collected papers represent part of the output from an intensive study conducted between September 1984 and March 1985 in Bangladesh and Washington, D.C. The study was a collaborative effort commissioned by the Bangladesh Ministry of Agriculture and organized by the International Food Policy Research Institute (IFPRI) and the Bangladesh Institute of Development Studies (BIDS).